Les besoins d’éducation à la carrière pour les élèves des écoles primaires et secondaires selon des conseillers d’orientation - Marceau, Denis (Canadian Journal of Counselling and Psychotherapy, 2011)
This article reports an assessment of career education needs from the point of view of 67 guidance counsellors working in the central part of Quebec primary and secondary schools. Most of these guidance counsellors support the importance of career education in schools; they consider that career education has to be a community effort. However, less of these counsellors accept that teachers and employers accomplish a kind of work traditionally done by guidance counselors.